Does the COVID-19 pandemic period itself increases early mortality rates of elderly patients with hip fractures in Turkey?. Issue 44 (5th November 2021) - Bilgetekin, Yenel Gürkan; Öztürk, Alper; Yüksel, Sinal; Kunu, Orhan; Atilla, Halis Atil; Ersan, Önder
Abstract : Abstract: Hip fractures are common in elderly patients and prone to serious morbidity and mortality particularly when the treatment is delayed. The objective of this study was to evaluate the effect Coronavirus disease of 2019 (COVID-19) pandemic on the early mortality rates of geriatric patients with hip fractures. 281 patients who were followed and operated on with the diagnosis of proximal femur fracture were included in this retrospective study. Patients were divided into 2 groups, that is, 180 patients presenting between March and June 2018 to 2019 (prepandemic period) and 101 patients presenting between March and June 2020 (pandemic period). Age, sex, type of fracture, time from fracture to presentation to hospital, comorbidities, time from admission to operation, length of intensive care unit stay, length of hospital stay, and mortality rates were retrieved from hospital records and evaluated. While there was no significant difference in terms of age, sex, type of fracture, in-hospital mortality, 30-day mortality, time to surgery, Charlson comorbidity index and length of intensive care unit stay through pandemic and prepandemic period ( P  > .05), significant differences were observed in terms of length of hospital stay, time to admission, refusal of hospitalization and attending outpatient visits regularly ( P  < .05). Attending outpatient visits and the length of hospital stay were the main significant differences in multivariate analysis. The early mortality rates in patients with hip fractures were similar during the pandemic period to before in Turkey. However, the length of hospital stay was prolonged and more patients refused the treatment and fewer of them attended regular outpatient controls in the pandemic.